Pengaruh Intensitas R&D, Keputusan Investasi, Keputusan Pendanaan dan Kebijakan Dividen Terhadap Nilai Perusahaan Manufaktur di Bursa Efek Indonesia Periode 2018-2022 - Hidayati, Diah; Meidiaswati, Harlina (Universitas Negeri Surabaya, 2024)
This study examines the effect of R&D intensity, investment decisions, funding decisions and dividend policy on firm value. This study measures firm value by Price to Book Value (PBV). The population in this study consisted of 228 manufacturing industry sector companies listed on the Indonesia Stock Exchange (IDX), and financial reports were published annually from 2018 to 2022. The sample used in this study consisted of 14 companies, with sampling techniques through purposive sampling. The research method used in this study is quantitative and is categorised into descriptive research. The data analysis techniques use multiple linear regression. The results showed funding decisions have a significant negative effect, while investment decisions and dividend policies have a significant positive effect on firm value. Meanwhile, R&D intensity does not affect firm value. Therefore, researchers suggest using investment decisions, funding decisions, and dividend policies that affect firm value as considerations when making good investment decisions and getting the most profit.